Seroprevalence of Human Papillomavirus (HPV) Type 6, 11, 16, 18, by Anatomic Site of HPV Infection, in Women Aged 16-64 Years living in the Metropolitan Area of San Juan, Puerto Rico - Pérez-Caraballo, Aixa M.; Suarez, Erick; Unger, Elizabeth R.; Palefsky, Joel M.; Panicker, Gitika; Ortiz, Ana Patricia (Puerto Rico Health Sciences Journal, 2018)
Objective: It is unknown if human papillomavirus (HPV) serum antibody responses vary by anatomic site of infection. We aimed to assess the seroprevalence for HPV 6, 11, 16 and 18 in association with HPV DNA detection in different anatomic sites among women. Methods: This cross sectional population-based study analyzed data from 524 women aged 16-64 years living in the San Juan metropolitan area of Puerto Rico (PR). Questionnaires were used to assess demographic and lifestyle variables, while anogenital and blood samples were collected for HPV analysis. Logistic regression models were used to estimate the adjusted prevalence odds ratio (POR) in order to determine the association between HPV DNA infection status in the cervix and anus and serum antibody status, controlling for different potential confounders. Results: Overall, 46.9% of women had detectable antibodies to one or more types whereas 8.7% had HPV DNA for one or more of these types detected in cervix (4.0%) or anus (6.5%). Women with cervical HPV detection tended to be more HPV seropositive than women without cervical detection (adjusted POR (95%CI): 2.41 (0.90, 6.47), p=0.078); however the type-specific association between cervical DNA and serum antibodies was only significant for HPV 18 (adjusted POR (95% CI): 5.9 (1.03, 33.98)). No significant association was detected between anal HPV and seropositivity (p>0.10). Conclusion: Differences in the anatomic site of infection could influence seroconversion, however, longitudinal studies will be required for further evaluation. This information will be instrumental in advancing knowledge of immune mechanisms involved in anatomic site response.